EPISTIMOLOGI MANAJEMEN DI ERA KEMAJUAN ISLAM - Nayyif Sujudi; Nabil Nabil (Almarhalah | Jurnal Pendidikan Islam, 2021)
AbstractIn the context of Islam, science is the beginning of human substance in building world civilization. Islamic epistemology has similarities with the term science in Western epistemology. Just as science in Western epistemology is distinguished from knowledge, science in Islamic epistemology is distinguished from opinion (ra'y). Science is not arbitrary knowledge or just opinion, but knowledge that has been tested for truth. The understanding of science is actually not much different from science, only science is limited to physical or sensory fields, science goes beyond it in non-physical fields such as metaphysics. Historical metamorphosis is added to analysis and management knowledge. Muslim philosophers are used as a basic reference as the core paradigm of management based on humanity and human patterns.Â Keywords: Epistemology, Muslim Philosophers, Islamic Management Orientation